Comorbidities do not limit improvement in pain and physical function after total knee arthroplasty in patients with knee osteoarthritis: the BEST-Knee prospective cohort study. Issue 6 (18th June 2021) - King, Lauren K; Waugh, Esther J; Jones, C Allyson; Bohm, Eric; Dunbar, Michael; Woodhouse, Linda; Noseworthy, Thomas; Marshall, Deborah A; Hawker, Gillian A
Abstract : Objective: To assess the relationship between comorbidities and amount of improvement in pain and physical function in recipients of total knee arthroplasty (TKA) for knee osteoarthritis (OA). Design: Prospective cohort study. Setting: Two provincial central intake hip and knee centres in Alberta, Canada. Participants: 1051 participants (278 in 6-minute walk test (6MWT) subset), ≥30 years of age with primary knee OA referred for consultation regarding elective primary TKA; assessed 1 month prior and 12 months after TKA. Primary and secondary outcome measures: Pre-post TKA change in knee OA pain (Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC)), physical function (Knee injury and Osteoarthritis Outcome Score (KOOS) Physical Function Short-Form) and 6MWT walking distance; and the reporting of an acceptable symptom state (Patient Acceptable Symptom State (PASS)) at 12 months after TKA. Results: Mean participant age was 67 years (SD 8.8), 59% were female and 85% reported at least one comorbidity. Individuals with a higher number of comorbidities had worse pre-TKA and post-TKA scores for pain, physical function and 6MWT distance. At 12-month follow-up, mean changes in pain, function and 6MWT distance, and proportion reporting a PASS, were similar for those with and without comorbidities. In multivariable regression analysis, adjusted for potential confounders and clustering by surgeon, no specific comorbidities nor total number of comorbidities were associated with less improvement in pain, physical function or 6MWT distance at 12 months after TKA. Patients with diabetes (OR 0.64, 95% CI 0.44 to 0.94) and a higher number of lower extremity troublesome joints (OR 0.85, 95% CI 0.76 to 0.96) had lower odds of reporting a PASS. Conclusion: For individuals with knee OA, comorbid conditions do not limit improvement in pain, physical function or walking ability after TKA, and most conditions do not impact achieving an acceptable symptom state.